Acute intermittent hypoxia induced neural plasticity in respiratory motor control. (23rd August 2013) - Xing, Tao; Fong, Angelina Y; Bautista, Tara G; Pilowsky, Paul M
Summary: Respiratory neural networks can adapt to rapid environmental change or be altered over the long term by various inputs. The mechanisms that underlie the plasticity necessary for adaptive changes in breathing remain unclear. Acute intermittent hypoxia (AIH)‐induced respiratory long‐term facilitation (LTF) is one of the most extensively studied types of respiratory plasticity. Acute intermittent hypoxia‐induced LTF is present in several respiratory motor outputs, innervating both pump muscles (i.e. diaphragm) and valve muscles (i.e. tongue, pharynx and larynx). Long‐term facilitation is present in various species, including humans, and the expression of LTF is influenced by gender, age and genetics. Serotonin plays a key role in initiating and modulating plasticity at the level of respiratory motor neurons. Recently, multiple intracellular pathways have been elucidated that are capable of giving rise to respiratory LTF. These mainly activate the metabolic receptors coupled to Gq ('Q' pathway) and Gs ('S' pathway) proteins. Herein, we discuss AIH‐induced respiratory LTF in animals and humans, as well as recent advances in our understanding of the synaptic and intracellular pathways underlying this form of plasticity. We also discuss the potential to use intermittent hypoxia to induce functional recovery following cervical spinal injury.